2020
DOI: 10.1016/j.celrep.2020.01.059
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Drug Screening Identifies a Potent Wnt Inhibitor that Promotes Airway Basal Stem Cell Homeostasis

Abstract: Graphical Abstract Highlights d A dysregulated Wnt/b-catenin axis in human lung premalignancy can be modeled in vitro d High-throughput drug screening identifies the Wnt/b-catenin inhibitor WIC1 d Low-dose treatment with WIC1 promotes differentiation to the ciliated cell fate d WIC1 acts to repress phosphorylation of b-catenin Y489 and Tp63 expression SUMMARYMechanisms underpinning airway epithelial homeostatic maintenance and ways to prevent its dysregulation remain elusive. Herein, we identify that b-catenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Haas et al demonstrated that high Wnt signaling triggers transcription of Tp63 , which then acts as a master regulator of basal cell stemness 66 . A recently identified novel Wnt signaling inhibitor can promote restoration of Wnt-induced dysregulation of proximal airway homeostasis via p-β-catenin Y489 /TP63-related mechanisms 65 (Fig. 3b ), further implicating the importance of the pathway in proximal airway homeostasis.…”
Section: Proximal Airway Homeostasis and Regenerationmentioning
confidence: 82%
See 3 more Smart Citations
“…Haas et al demonstrated that high Wnt signaling triggers transcription of Tp63 , which then acts as a master regulator of basal cell stemness 66 . A recently identified novel Wnt signaling inhibitor can promote restoration of Wnt-induced dysregulation of proximal airway homeostasis via p-β-catenin Y489 /TP63-related mechanisms 65 (Fig. 3b ), further implicating the importance of the pathway in proximal airway homeostasis.…”
Section: Proximal Airway Homeostasis and Regenerationmentioning
confidence: 82%
“…While Wnt signaling promotes ciliated cell differentiation, this is not true at all doses of pathway activation 65 . In contrast, high levels of Wnt signaling drive ABSC hyperproliferation concomitant with a phosphorylated form of nuclear β-catenin at Y489 (p-β-catenin Y489 ) and abolishment of differentiation to the ciliated cell fate 65 (Fig. 3b ).…”
Section: Proximal Airway Homeostasis and Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…β -Catenin has been thought to be involved in the regulation of cell fate, such as proliferation, differentiation, and apoptosis or T cell development [ 16 , 17 ]. In most published studies, β -catenin has a close association with the pathogenesis of malignant diseases and is a therapeutic target for cancer in view of its function to promote tumor cell proliferation [ 18 ].…”
Section: Discussionmentioning
confidence: 99%